Understanding Cultural Fidelity. (14th April 2019) - Charbonneau, Mathieu
Abstract: A leading idea of cultural evolutionary theory is that for human cultures to undergo evolutionary change, cultural transmission must generally serve as a high-fidelity copying process. In analogy to genetic inheritance, the high fidelity of human cultural transmission would act as a safeguard against the transformation and loss of cultural information, thus ensuring both the stability and longevity of cultural traditions. Cultural fidelity would also serve as the key difference-maker between human cumulative cultures and non-human non-cumulative traditions, explaining why only us humans, with our uniquely high-fidelity transmission capabilities, are capable of evolving and sustaining complex traditions. But what does it mean for cultural transmission to be more or less faithful? This article has two objectives. The first is to clarify the meaning and uses of the concept of cultural fidelity and to evaluate their explanatory import. I argue that cultural evolutionists use several fidelity concepts (episodic, propensity, and generalized fidelity), concepts that I will define and clarify. The second objective is to challenge the explanatory significance of a general notion of fidelity (generalized fidelity) as being both explanatorily meaningful and operationalizable. I conclude that if fidelity is to serve as an explanation of the key differences between human cumulative cultures and non-human non-cumulative traditions, then the concept will have to be redesigned and rely on different assumptions. 1 Introduction 2 Generalized Fidelity 2.1 The need for an explanatory concept of fidelity 2.2 Three conditions for a general notion of cultural fidelity 3 Episodic Fidelity 3.1 Measuring episodic fidelity 3.2 The relevance problem 3.3 Explanatory pluralism 3.4 The incommensurability of fidelity metrics 4 Propensity Fidelity 5 Fidelity as an Explanatory Concept 5.1 Explaining cultural stability 5.2 Explaining human distinctiveness 6 Conclusion